2021
DOI: 10.4236/ojmn.2021.114026
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Extradural Hematoma Patients in Relation to Preoperative Neurological Status

Abstract: Introduction: Epidural hematoma (EDH) is characterized by the acute onset of traumatic haemorrhage into potential space between the dura mater and skull following head injury. About 85% of the epidural cases are caused by skull fracture with rupture of the middle meningeal artery or its branches and rest of 1the time ruptured venous sinuses, fractured diploic bone. The BTF recommends that all patients with an EDH volume of greater than 30 cc should undergo surgical evacuation regardless of Glasgow Coma Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Khaled et al 5 found that the time interval between trauma and surgery was within 13 to 24 hours in 54% of their cases. In Howlader et al 13 study, 66.31% of patients underwent surgery within 6 to 24 hours after trauma. In Niaz et al 14 study, 70.0% of patients had EDH evacuation in less than 6 hours after injury.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Khaled et al 5 found that the time interval between trauma and surgery was within 13 to 24 hours in 54% of their cases. In Howlader et al 13 study, 66.31% of patients underwent surgery within 6 to 24 hours after trauma. In Niaz et al 14 study, 70.0% of patients had EDH evacuation in less than 6 hours after injury.…”
Section: Discussionmentioning
confidence: 97%
“…This study was approved by the local ethical scientific committee of our institution (IRB approval number: 4-2023.NEUS 4-1). Head injury patients of either sex with no age restrictions who presented with GCS score (4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and had acute EDH with volume ! 40 cm 3 on brain CT scan were included in our study.…”
Section: Study Design and Patients' Populationmentioning
confidence: 99%